The athlete's guide to diabetes - Colberg, Sheri 1963- (Champaign, IL Human Kinetics, 2020)
Diabetes doesn't have to slow you down. Whether you're a recreational exerciser or a competitive athlete, The Athlete's Guide to Diabetes has the training and performance advice you need to remain active while effectively managing your condition. Renowned researcher and diabetes expert Dr. Sheri Colberg offers best practices and tips for managing blood glucose levels for athletes of all ages with type 1 and type 2 diabetes. She provides the most up-to-date information on insulin and other medications and their effects on exercise, nutritional practices and supplements, including low-carbohydrate eating, the latest technologies used to manage glucose, including continuous glucose monitoring (CGM), injury prevention and treatment as well as tactics for diabetes-related joint issues, and mental strategies for maximizing performance and optimizing health. You'll find 15 profiles of athletes with type 1 diabetes who share their accomplishments and how they manage medications, food intake, and other tools available to manage their activities with diabetes. Guidelines for 165 different sports and activities will reduce your trial and error when it comes to performing and feeling your best during fitness activities, endurance sports, endurance-power sports, power sports, and outdoor activities. The Athlete's Guide to Diabetes adheres to latest guidelines from such trusted sources as the American Diabetes Association and the American College of Sports Medicine. It is the one resource you can't be without if you want to stay healthy and active, train smarter, and reach new levels of athletic success without losing control of your blood glucose management.
Part I. Diabetic Athlete's Toolbox -- Chapter 1. Training Basics for Fitness & Sports -- Chapter 2. Balancing Exercise Blood Glucose -- Chapter 3. Ups and Downs of Insulin and Other Medications -- Chapter 4. Eating Right and Supplementing for Activity -- Chapter 5. Using Technology and Monitoring to Enhance Performance -- Chapter 6. Thinking and Acting Like an Athlete -- Chapter 7. Preventing and Treating Athletic Injuries -- Part II. Guidelines for Specific Activities -- Chapter 8. Fitness Activities -- Chapter 9. Endurance Sports -- Chapter 10. Endurance-Power Sports -- Chapter 11. Power Sports -- Chapter 12. Outdoor Recreation and Sports -- Appendix A. Diabetes, Sports, and Related Organizations -- Appendix B. Diabetes, Sports, and Nutrition Websites.
Revision of Diabetic athlete's handbook
Includes bibliographical references
Keywords: Diabetic athletes -- Handbooks, manuals, etc; Diabetes -- Exercise therapy -- Handbooks, manuals, etc